PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN SPBU PERTAMINA GUNUNG ANYAR - Lailatus Zuhro (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine how service quality and price influence customer satisfaction at Pertamina's Gunung Anyar gas station. A quantitative methodology was used, including distributing a survey to 130 randomly selected individuals. The independent variables identified were service quality (X1) and price (X2), while the dependent variable was customer satisfaction (Y). Data analysis used validity and reliability tests, classical assumption evaluation, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The research findings indicate that service quality has a significant and positive impact on customer satisfaction. Furthermore, price also significantly influences customer satisfaction. Both service quality and price together have a significant influence on customer satisfaction, with the R² value reflecting the substantial contribution of these two factors in explaining differences in customer satisfaction levels.